Study on genetic diversity of pointed gourd using morphological characters (Bangladesh Journal of Agricultural Research, 2009)
The genetic diversity among 64 pointed gourd genotypes were assessed through multivariate analysis from an experiment conducted in Regional Agricultural Research Station, lshurdi, Pabna during the growing season 2002-2003. The genotypes were grouped into twelve clusters. The cluster V consisted of highest number of genotypes and it was nine, the cluster VI and cluster VIII contained the lowest number of genotypes and it was two in each. The clustering pattern of the genotypes under this study revealed that the genotypes collected from the same location were grouped into different clusters. The genotypes of Jessore were distributed in different clusters. The highest inter genotype distance as 366.3 observed between the genotypes P0022 and P0007 and the lowest 2.6 as observed between the genotypes P0043 and P0044. Cluster V had the highest cluster mean value for internode length, fruit weight per plant and yield the highest inter-cluster distance was noticed between cluster III and II (45.71) and the lowest between cluster VII and VI (3.33). âThe highest intra cluster distance was computed for cluster III and that was lowest for the cluster II. The first five axes accounted for 77.65% of the total variation among the 13 characters describing 64 pointed gourd genotypes. Fruit weight, seeds per fruit and fruit weight per plant contributed maximum to the total divergence. The results obtained by D2 analysis were confirmed by canonical analysis. Key Words: Diversity pointed gourd, morphological characters. doi: 10.3329/bjar.v33i4.2304 Bangladesh J. Agril. Res. 33(4) : 607-616, December 2008